PENDAMPINGAN MASYARAKAT PUTUS SEKOLAH DAN TIDAK MAMPU GUNA MENINGKATKAN TARAF EKONOMI KELUARGA MELALUI PROGRAM PENUNTASAN WAJIB BELAJAR 12 TAHUN DI PKBM JAYA KESUMA - Arif Darmawan; Nairobi Nairobi; Tedy Rusman; Novriyanti Novriyanti; Widia Anggi Palupi (Politeknik Negeri Sriwijaya, 2022)
To help the government to make the 12-year compulsory education program a success, the University of Lampung community service team took the initiative to assist in delivering education to people who have dropped out of school and have economic difficulties by cooperating with partners in the form of a local non-formal educational institution called PKBM Jaya Kusuma who is domiciled in Langkapura Village, Bandar Lampung City. The activities to be carried out are in the form of knowledge transfer and life skills regarding good and correct teaching techniques, delivery of basic education according to education levels using participatory methods, starting from problem formulation with partners, surveying potential areas, and implementing mentoring practices, as well as trying to help market this institution. To control the success and progress of activities, monitoring and evaluation are carried out. This activity is expected to produce several outcomes, namely (1) the community educated by PKBM Jaya Kusuma can fill their minds with useful and beneficial knowledge; (2) the community can become agents of educational change by disseminating the results of the PKBM education to the community around their homes who have the same conditions as them so that they can improve the quality of the people there; and (3) PKBM Jaya Kusuma is increasingly recognized and developed as a non-formal educational institution capable of producing quality human resources capable of being useful for the surrounding environment and the country as well as being able to improve the economic conditions of their families.